2016
DOI: 10.3389/fpls.2016.01626
|View full text |Cite
|
Sign up to set email alerts
|

Control of Wilt and Rot Pathogens of Tomato by Antagonistic Pink Pigmented Facultative Methylotrophic Delftia lacustris and Bacillus spp.

Abstract: The studies on the biocontrol potential of pink pigmented facultative methylotrophic (PPFM) bacteria other than the genus Methylobacterium are scarce. In the present study, we report three facultative methylotrophic isolates; PPO-1, PPT-1, and PPB-1, respectively, identified as Delftia lacustris, Bacillus subtilis, and Bacillus cereus by 16S rRNA gene sequence analysis. Hemolytic activity was tested to investigate the potential pathogenicity of isolates to plants and humans, the results indicates that the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The ability of Delftia strains to fix atmospheric nitrogen, and produce phytohormones, siderophores, antifungal compounds (heterocyclic N) and 1-aminocyclopropane-1- carboxylate (ACC) deaminase, solubilize phosphate and perform sulfur oxidation, was reported by Banach et al and Brana et al [38,39]. Delftia strains have been reported as plant growth promotors of many plants, including rice, tomato and some legumes [40,41,42,43,44]. Morel et al [40,41] reported that strain Delftia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of Delftia strains to fix atmospheric nitrogen, and produce phytohormones, siderophores, antifungal compounds (heterocyclic N) and 1-aminocyclopropane-1- carboxylate (ACC) deaminase, solubilize phosphate and perform sulfur oxidation, was reported by Banach et al and Brana et al [38,39]. Delftia strains have been reported as plant growth promotors of many plants, including rice, tomato and some legumes [40,41,42,43,44]. Morel et al [40,41] reported that strain Delftia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, strain HR4 also showed a high nitrogen-fixing activity. The potential of bacteria genus Delftia to inhibit the growth of tomato ( Lycopersicon esculentum ) pathogens Fusarium , Sclerotium , Pythium and Rhizoctonia was also noted [44].…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis is a Gram-positive soil bacterium used as a highly efficient biocontrol agent, protecting plants from both fungal and bacterial pathogens (16)(17)(18)(19)(20). This protection is proposed to be mediated by the formation of robust biofilms (7,21) and by the production of a wide range of antibiotics (22) that shape interspecies interactions (23).…”
mentioning
confidence: 99%
“…lacustris were detected, and others similar to S. maltophilia were detected in wheat rhizosphere. D. lacustris (methylotrophic isolate) showed direct antifungal properties, while its antibacterial potential may be attributed to volatile inhibitory compounds and/or induction of systemic resistance (ISR) (Janahiraman et al 2016). The pathogen was undetectable in the second-year corn soil and rhizosphere, which coincided with an increase in oligotrophic bacteria along with the detection of a new strain similar to Beijerinckia fluminensis in corn soil.…”
Section: Pathogen Density In Different Habitats Before and After Planmentioning
confidence: 99%